FLOOD HAZARDOUS ANTICIPATION (CASE STUDY : KAMPUNG MELAYU AND KELAPA GADING RESIDENCES, JAKARTA, INDONESIA) - Hotniar Siringoringo (Universitas Gunadarma, 2011)
The objective of this research is to identify flood hazardous anticipation of inhabitants who live in two locations in Jakarta Indonesia, i.e. Kampung Melayu and Kelapa Gading, which are flood stricken most frequently. A self-administered questionnaire was prepared. Questionnaire consist of 15 items excludes respondents profile. Most of items were scored on 3 scales (no, perhaps, certainly), and some were scored on 2 scales (yes and no). In addition to that, questionnaire also assembled with demography questions. However, the participants to the survey were recruited through convenience sampling. That is, questionnaires were distributed to a person who is available at the time data collection. Data collected further was summarized using cross tabulation and analyzed using non parametric test SPSS to test the hypothesis. Flood hazard anticipation was measured using flood mitigation and intention to reduce the impact of flood. Result shows that there’s different flood mitigation and intention to reduce the impact of flood between in habitants in Kelapa Gading and Kampung Melayu. Inhabitants in Kampung Melayu seem more prepare for flooding in the future.